2015
DOI: 10.1002/2015wr017326
|View full text |Cite
|
Sign up to set email alerts
|

Flood‐type classification in mountainous catchments using crisp and fuzzy decision trees

Abstract: Floods are governed by largely varying processes and thus exhibit various behaviors. Classification of flood events into flood types and the determination of their respective frequency is therefore important for a better understanding and prediction of floods. This study presents a flood classification for identifying flood patterns at a catchment scale by means of a fuzzy decision tree. Hence, events are represented as a spectrum of six main possible flood types that are attributed with their degree of accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(160 citation statements)
references
References 78 publications
2
138
0
Order By: Relevance
“…Merz and Blöschl (2003) classified flood events across Austria based on climate inputs (rainfall, snowmelt) and basin states (soil moisture, snow cover). Sikorska et al (2015) classified flood events in mountainous Swiss catchments using characteristics of precipitation and catchment states, such as catchment wetness, snow cover and glacier cover. Turkington et al (2016) classified synthetic flood events generated through application of a weather generator together with a hydrological model by using a cluster analysis technique on a set 25 of meteorological indices derived from the generated synthetic weather for two Alpine catchments in France and Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Merz and Blöschl (2003) classified flood events across Austria based on climate inputs (rainfall, snowmelt) and basin states (soil moisture, snow cover). Sikorska et al (2015) classified flood events in mountainous Swiss catchments using characteristics of precipitation and catchment states, such as catchment wetness, snow cover and glacier cover. Turkington et al (2016) classified synthetic flood events generated through application of a weather generator together with a hydrological model by using a cluster analysis technique on a set 25 of meteorological indices derived from the generated synthetic weather for two Alpine catchments in France and Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall-runoff modeling implicitly creates spatial dependence between flows at different locations (Neal et al, 2013). However, the use of 30 a rainfall-runoff model compared to a statistical analysis of flow records, introduces additional sources of uncertainties such as model and parameter uncertainty of the hydrological model (Sikorska et al, 2015). Focusing on flood event data avoids complexity and reduces the number of uncertainty sources .…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case when using the clustering approach proposed in this study and the assignment of a catchment to one group or another is not necessarily straightforward. Similarly, Sikorska et al [2015] showed that flood events usually show partial memberships to more than one flood type. The clustering approach based on functional data proposed here could be transferred into a fuzzy setting [Rao and Srinivas, 2006;Tokushige et al, 2007;Sikorska et al, 2015] that would allow for catchments and hydrograph shapes with partial or distributed memberships to more than one region or event type.…”
Section: Use Of Reactivity Regions In Design Hydrograph Constructionmentioning
confidence: 96%
“…All rights reserved. previously developed classification schemes correspond to flash floods [Merz and Blöschl, 2003;Diezig and Weingartner, 2007;Sikorska et al, 2015]. They are characterized by rather high peak discharges and low hydrograph volumes.…”
Section: Identification Of Representative Hydrograph Shapesmentioning
confidence: 99%